Archives in the Clouds (Atlanti, 2016)
The issues of a guaranteed and orderly conservation of the archives, of all archives, is intertwined since ever, but even more in the digital world, with the issue of the confidentiality of data. The present work will retrace here briefly the principles already established in the Italian archival law of the ‘60s, but who went then gradually taking shape in the ‘90s of last century, when people began to talk about privacy, confidentiality, right to oblivion, sensitive and very sensitive data on the one hand and transparency, right of access and information on the other. If public administrations have already issued a regulation articulated both for the preservation of digital native documents as well as for their access, private archives are threatened by problems related to incorrect storage of data and the lightness with which they are entrusted to the web.
Keywords: conservation; safety; security; archives; digital data; social network